The influence of osteoporosis in femoral fracture healing time. - Nikolaou, Vassilios S; Efstathopoulos, Nicolas; Kontakis, George; Nikolaos K. Kanakaris; Giannoudis, Peter V (Injury, 2009)
AIM: In order to assess the effect of osteoporosis on healing time, the files of 165 patients with femoral shaft fractures that were treated in our institution with locked-reamed intramedullary nailing were retrospectively reviewed. PATIENTS AND METHODS: Patients with open fractures, pathological fractures, revision surgery, severe brain injuries and prolonged ITU stay were excluded. In all patients the Singh-index score for osteoporosis and the canal bone ratio (CBR) were assigned. Sixty-six patients fulfilled the inclusion criteria. Patients were divided into two groups; group A (29 patients) consisted of patients over 65 years old with radiological evidence of osteoporosis and group B (37 patients) of patients between 18 and 40 years old with no signs of osteoporosis. RESULTS: In all group A patients Singh score < or =4 and CBR>0.50 were assigned, suggesting the presence of osteoporosis, whereas all group B patients were assigned with Singh score > or =5 and CBR<0.48. Fractures of group A healed in 19.38+/-5.9 weeks (12-30) and in group B 16.19+/-5.07 weeks (10-28), P=0.02. CONCLUSIONS: Fracture healing of nailed femoral diaphyseal fractures is significantly delayed in older osteoporotic patients. Further studies are required to clarify the exact impact of osteoporosis in the whole healing process.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Bone Density; Diaphyses; Female; Femoral Fractures; Fracture Fixation, Intramedullary; Fracture Healing; Humans; Injury Severity Score; Male; Osteoporosis; Radiography; Retrospective Studies; Time Factors; Weight-Bearing; Young Adult